2021
DOI: 10.3389/fendo.2021.650883
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Conception and the Cumulative Pregnancy Rate in Subfertile Couples Undergoing Timed Intercourse With Ultrasound

Abstract: The aim of this study was to determine predictive factors for pregnancy and assess the cumulative pregnancy rate (CPR) and live birth rate (CLBR) in subfertile couples undergoing timed intercourse (TI) using ultrasound. This retrospective cohort study included 285 women (854 cycles) who started TI with ultrasound between January 2017 and October 2019. The overall clinical pregnancy rate was 28.1% (80/285) per couple and 9.4% (80/854) per cycle. Pregnant women had a higher body mass index (BMI), higher percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…This finding has not been reported yet in previous studies and is considered as a proceeding for our study. In addition, the duration of infertility was chosen as the basis for subgroup analysis as numerous investigations confirmed that the pregnancy rate was peculiarly compromised by it [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding has not been reported yet in previous studies and is considered as a proceeding for our study. In addition, the duration of infertility was chosen as the basis for subgroup analysis as numerous investigations confirmed that the pregnancy rate was peculiarly compromised by it [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%